Westonci.ca makes finding answers easy, with a community of experts ready to provide you with the information you seek. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the given problem, we need to simplify the expression [tex]\(\left(2^{\frac{1}{4}}\right)^4\)[/tex]. Let's go through each of the provided options and determine which one accurately simplifies the given statement.
### Option A:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2 \cdot \left(\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}\right)=2 \cdot \frac{4}{4}=2 \][/tex]
- Breaking down the expression multiplication [tex]\(2 \cdot \left(\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}\right)\)[/tex]: This misinterprets the multiplication of exponents. The statement here incorrectly doubles [tex]\(2\)[/tex], not respecting the rules of exponentiation correctly.
### Option B:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}}=2^{\frac{4}{4}}=2^1=2 \][/tex]
- Here, the product of the exponents is: [tex]\(2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}} = 2^{1} = 2\)[/tex]. This is the correct way to handle multiplication of like bases with exponents.
### Option C:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4}}=2^{\frac{4}{4}}=2^1=2 \][/tex]
- This option incorrectly uses multiplication of the exponents instead of adding them. The correct operation should be [tex]\(2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}} = 2^{1}\)[/tex].
### Option D:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=4 \cdot 2^{\frac{1}{4}}=4 \cdot \frac{1}{4} \cdot 2=2 \][/tex]
- This option incorrectly multiplies the result by 4 and introduces the mixup with the exponents. The simplification [tex]\(4 \cdot 2^{\frac{1}{4}}\)[/tex] and then [tex]\((2 \cdot \frac{1}{4}) = 2\)[/tex] is incorrect.
### Conclusion
After reviewing all the options, Option B correctly simplifies the expression:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}}=2^{1}=2 \][/tex]
Thus, the correct simplification is given in Option B.
### Option A:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2 \cdot \left(\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}\right)=2 \cdot \frac{4}{4}=2 \][/tex]
- Breaking down the expression multiplication [tex]\(2 \cdot \left(\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}\right)\)[/tex]: This misinterprets the multiplication of exponents. The statement here incorrectly doubles [tex]\(2\)[/tex], not respecting the rules of exponentiation correctly.
### Option B:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4}+\frac{1}{4}+\frac{1}{4}+\frac{1}{4}}=2^{\frac{4}{4}}=2^1=2 \][/tex]
- Here, the product of the exponents is: [tex]\(2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}} = 2^{1} = 2\)[/tex]. This is the correct way to handle multiplication of like bases with exponents.
### Option C:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4} \cdot \frac{1}{4}}=2^{\frac{4}{4}}=2^1=2 \][/tex]
- This option incorrectly uses multiplication of the exponents instead of adding them. The correct operation should be [tex]\(2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}} = 2^{1}\)[/tex].
### Option D:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=4 \cdot 2^{\frac{1}{4}}=4 \cdot \frac{1}{4} \cdot 2=2 \][/tex]
- This option incorrectly multiplies the result by 4 and introduces the mixup with the exponents. The simplification [tex]\(4 \cdot 2^{\frac{1}{4}}\)[/tex] and then [tex]\((2 \cdot \frac{1}{4}) = 2\)[/tex] is incorrect.
### Conclusion
After reviewing all the options, Option B correctly simplifies the expression:
[tex]\[ \left(2^{\frac{1}{4}}\right)^4=2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}} \cdot 2^{\frac{1}{4}}=2^{\frac{1}{4} + \frac{1}{4} + \frac{1}{4} + \frac{1}{4}}=2^{1}=2 \][/tex]
Thus, the correct simplification is given in Option B.
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.